PENINGKATAN KETRAMPILAN SISWA PADA MATA PELAJARAN DASAR KOMPUTER DAN JARINGAN MENGGUNAKAN MEDIA PEMBELAJARAN VIRTUAL MACHINE - Saputro, Fajar Adil (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The low number of students in class X Creative 2 TJKT SMK Muhammadiyah 2 Andong who have skills competencies for basic computer and network subjects with the theme of operating systems. This study aims to improve the skills of students of class X Creative 2 TJKT SMK Muhammadiyah 2 Andong through Virtual Box oracle virtual machine learning media. This study involved 18 students with a cycle that included planning, implementation, observation and reflection. The research method used is Classroom Action Research or what is often called Classroom Action Research. Data collection techniques were carried out using observation and interview methods. The results showed that there was an increase in the number of students who had competency skills in Basic Computer and Networking lessons with the theme of operating systems before and after using Virtual Box oracle virtual machine learning media. From previously 2 students or about 12% to 6 students or about 34% of the total number of students as many as 18 students. According to the results of the discussion, the conclusion that can be drawn is that the use of Virtual Box oracle virtual machine learning media can improve the skills of installing operating systems for students in basic computer and network subjects with the theme of operating systems.